Metabolic landscape uncovers remodeling of T cell immunity affected by fatty acid desaturase in Parkinson’s disease at single-cell resolution - Shi Yan; Xue Zhao; Yao Si; Xinyu Zhang; Di Wang; Lifen Yao; Linlin Sun (BMC Biology)
Abstract Background Peripheral activated T cells cross the blood–brain barrier, partake in neuroinflammation, and induce dopaminergic neuron degeneration through characteristics such as cell adhesion and immune response in Parkinson’s disease (PD). Metabolic activity, which can regulate and be regulated by cellular signaling pathways, has a profound impact on the differentiation and function of T cells. However, a characterization of T-cell metabolic heterogeneity at single-cell resolution in PD is still lacking. Here, combining metabolic gene expression profiling and pathway activity algorithm, we studied the metabolic programs in PD-associated T cells. Results Cytotoxic T cells (CTLs) with adhesive properties dominated the proportion in PD patients based on the distribution of T cell types at single-cell resolution. The unsaturated fatty acid (UFA) biosynthetic process was found to be the pivotal contributor to CTLs’ metabolic features distinct from other cell types. Meanwhile, the upregulation of UFA biosynthetic process strongly correlated with immunologic activity in CTLs. Additionally, we revealed that fatty acid desaturases became the critical factor in determining CTLs’ metabolic heterogeneity according to the differentiation of T cell lineage and the high expression of metabolic genes in PD. Subsequent fatty acid desaturases adjustments mediated crosstalk with CTLs’ immunity, suggesting a potential target for regulating neuroinflammation in PD condition. Conclusions This analysis decoded the activation of T cells from another perspective, where PD-associated CTLs were metabolically reprogrammed to interact with the immune system, for in-depth insights into the immune characteristics of PD.